The Contextualization of Spiritual Warfare in Nigeria: An Assessment of the Ministry of Garrick Braide - Karibo, Innocent (NIU Journal of Humanities, 2025)
Spiritual warfare occupies a central place in Nigerian Christianity, reflecting the complex interplay between African cosmologies, socio-political realities, and Christian theological frameworks. It involves struggles against spiritual oppression and the pursuit of communal well-being, resonating with African religious consciousness where material and spiritual realms are closely intertwined. This study examines spiritual warfare through the prophetic ministry of Garrick Sokari Braide (1882–1918), a pioneer of African Indigenous Christianity whose work emphasized healing, deliverance, and moral reform. Braide challenged colonial missionary authority, affirmed African Christian identity, and framed spiritual engagement as both religious devotion and socio-political resistance. Using a historical-analytical approach that draws on archival materials, oral traditions, and secondary literature, the paper critically assesses contemporary practices that often reduce spiritual warfare to fear-driven rituals or prosperity-focused pursuits prioritizing individual gain. By retrieving Braide’s model, the study proposes a balanced paradigm for contextual Christian praxis that integrates biblical faith, African cosmology, and social responsibility. Revisiting Braide’s legacy offers Nigerian Christianity an ethically informed and socially responsive framework, transforming spiritual warfare from a superficial or exploitative practice into a practice that nurtures communal resilience, moral integrity, and holistic liberation. Keywords: Spiritual Warfare, Garrick Sokari Braide, Nigerian Christianity, African Indigenous Christianity, Contextual Theology, Communal Liberation.